Body composition parameters correlate with the endoscopic severity in Crohn’s disease patients treated with infliximab - Tang, Wuli; Xie, Gang; Li, Junlin; Tan, Wei; Yi, Rongqi; Yang, Ling; Zhang, Lingqin; Deng, Jiaxing; Zhang, Yue; Li, Kang (Frontiers in Nutrition, 2023)
The disease activity status and behavior of Crohn's disease (CD) can reflect the severity of the disease, and changes in body composition are common in CD patients.The aim of this study was to investigate the relationship between body composition parameters and disease severity in CD patients treated with infliximab (IFX).Methods: Patients with CD assessed with the simple endoscopic score (SES-CD) and were treated with IFX were retrospectively collected, and body composition parameters at the level of the 3rd lumbar vertebrae were calculated from computed tomography (CT) scans of the patients. The correlation of patients' body composition parameters with disease activity status and disease behavior was analyzed, and the diagnostic value of the relevant parameters was assessed using receiver operating characteristic (ROC) curves.